Ferromagnetism at room temperature in activated graphene oxide - Raj, K. Govind; Joy, Pattayil Alias (Chemical Physics Letters, 2014)
High room temperature ferromagnetic moment with high Curie temperature (>700 K) for graphene oxide (GO) is obtained by a simple chemical activation using phosphoric acid followed by heat treatment at 800 degrees C. The field and temperature variations of the magnetization data indicate ferromagnetic, paramagnetic and diamagnetic contributions in the acid/heat treated sample. IR spectroscopic studies suggest hydrogenation (reduction) of GO after the acid and heat treatments. The results point to the role of defects, extent of hydrogenation, changes in the bonding characteristics and the nature of the functional groups in determining the different magnetic contributions. (C) 2014 Elsevier B.V. All rights reserved.